(untitled) (مجلة الواحات للبحوث والدراسات, 2025)
Delete the character or the tool in the Koran leads to a rhetorical purposes and different semantics understood by the listener from the context of the speech, and this is in the rules of discourse in the Arabic language in which the deletion leads to aspects of rhetoric understood by the listener. And context helpsto guide and determine the intended meaning of the speech.